2000
DOI: 10.1097/00001756-200005150-00022
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex activation associated with octave illusion

Abstract: Nerve growth factor (NGF) promotes the survival of several neuronal populations, but recently it has also been shown to induce neuronal cell death. Here we report the effects of NGF on lesioned motoneurons. We have analyzed facial and sciatic motoneurons in newborn and adult BALB/c and C57BL/6 mice, in addition to mice deficient in the low-affinity p75 receptor for the neurotrophins (p75NTR). NGF application did not alter survival of lesioned facial motoneurons in any of the strains examined independent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 3 publications
3
26
0
Order By: Relevance
“…As the site of the main auditory cortex, the temporal lobe is responsible for processing dichotic signals [24,25], and for processing the octave illusion [27]. Our results also demonstrated that this area was synchronized with the frontal region when processing the octave illusion, which was concurrent with other EEG findings, so that the frontal (especially the mediofrontal) area is activated when processing auditory stimuli [45,54].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As the site of the main auditory cortex, the temporal lobe is responsible for processing dichotic signals [24,25], and for processing the octave illusion [27]. Our results also demonstrated that this area was synchronized with the frontal region when processing the octave illusion, which was concurrent with other EEG findings, so that the frontal (especially the mediofrontal) area is activated when processing auditory stimuli [45,54].…”
Section: Discussionsupporting
confidence: 81%
“…There was also no statistically significant group-difference of the task-related coherence differences of intra-temporal (F [1,27] …”
Section: Reporting Left (N = 11) Reporting Right (N = 18)mentioning
confidence: 86%
See 1 more Smart Citation
“…Lamminmaki and Hari (2000) conducted a study using magnetoencephalography (MEG) and suggested that the location of the N100m component of the auditory evoked field corresponds to the perceived locations of the tones elicited by the illusory stimulus rather than their actual locations. However, there is debate in the literature about both the generators and the functional significance of the N100m component(s).…”
mentioning
confidence: 99%
“…Lamminmaki and Hari (2000) focused on the where component. Using MEG, they recorded responses to 400-Hz and 800-Hz tones that were presented in different combinations at the two ears.…”
Section: B the Octave Illusionmentioning
confidence: 99%